Renal Tubular Acidosis - Surjit Tarafdar; Adrienne Cohen (Australasian Journal of Clinical Nephrology, 2026)
Renal tubular acidosis (RTA) refers to a group of disorders characterized by impaired renal acid excretion, resulting in normal anion gap (hyperchloremic) metabolic acidosis with either hypokalaemia or hyperkalaemia and a relatively well preserved GFR. Proximal RTA (type 2 RTA) is caused by reduced ability to reabsorb HCO3- in the proximal tubules while distal RTA (type 1 RTA) is caused by a defect in distal H+ ion excretion. Type 1 RTA is characteristically associated with urinary pH more than 5.5 while the urine pH is less than 5.5 in type 2 RTA. Sjogren’s syndrome has a strong association with type 1 RTA. One must always consider myeloma in the differential in patients presenting with type 2 RTA. While both conditions are treated with alkali and potassium replacement, type 2 RTA often needs larger doses of alkali, which can cause worsening hypokalaemia. In these patients, and the type 1 RTA patients who are recurrent renal calcium stone formers, one can use potassium citrate for alkali replacement. Type 4 RTA is most commonly caused by aldosterone deficiency or tubular resistance to the action of aldosterone. It is common in those with diabetes and is also associated with drugs which interfere with the RAAS pathway i.e., ACEI or ARB, as well as aldosterone antagonists such as spironolactone. While synthetic mineralocorticoids such as fludrocortisone are effective, in patients with hypertension or fluid overload, thiazide or loop diuretics may be helpful.